Rural Society, Agriculture and Settlement Territory in the Roman, Medieval and Modern Period Pilis Landscape - Simon, Bence (Dissertationes Archaeologicae, 2020)
This study presents how the scientific results of economic geography can be useful in explaining and deepening our understanding of the settlement pattern, village territory or land-use regarding the Roman, Medieval and Modern period Pilis landscape. Through ordinary comparison and GIS-based investigations the relationship of the studied periods is at the paper’s focus. In the last part, the study introduces a method with which the origins of the present-day administrative boundaries can be explored in a new way.